2002
DOI: 10.1055/s-2002-33670
|View full text |Cite
|
Sign up to set email alerts
|

Sub- und postpartales Management von Patientinnen mit von-Willebrand-Jürgens-Syndrom Typ 2B

Abstract: Von Willebrand's disease (VWD) is the most common congenital haemorrhagic diathesis inherited as an autosomal dominant trait, with a prevalence estimated to be 1 - 2 %. In subtype 2B an abnormally structured von-Willebrand factor (VWF) leads to an increased binding of VWF molecules to normal platelets, which regularly results in thrombocytopenia in pregnancy. Only few systematic observations in patients with type 2B VWD in the perinatal period have been reported in the literature. Six spontaneous deliveries in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Güth et al [4 ]reported 6 pregnancies and spontaneous deliveries in 2 sisters with 2B von Willebrand disease. One delivered 5 children with no factor support.…”
Section: Discussionmentioning
confidence: 99%
“…Güth et al [4 ]reported 6 pregnancies and spontaneous deliveries in 2 sisters with 2B von Willebrand disease. One delivered 5 children with no factor support.…”
Section: Discussionmentioning
confidence: 99%
“…Güth et al. [ 16 ] showed that the clinical management of pregnancy, delivery, and puerperium in patients with thrombocytopenia needs a close cooperation of experienced hematologists, obstetricians, anesthesiologists, pediatricians, and other specialists in this field. In parallel, Veneri et al.…”
Section: Management Of Thrombocytopenia In Obstetric Patientsmentioning
confidence: 99%